2017
DOI: 10.1002/mgg3.317
|View full text |Cite
|
Sign up to set email alerts
|

Targeted sequencing of 36 known or putative colorectal cancer susceptibility genes

Abstract: BackgroundMutations in several genes predispose to colorectal cancer. Genetic testing for hereditary colorectal cancer syndromes was previously limited to single gene tests; thus, only a very limited number of genes were tested, and rarely those infrequently mutated in colorectal cancer. Next‐generation sequencing technologies have made it possible to sequencing panels of genes known and suspected to influence colorectal cancer susceptibility.MethodsTargeted sequencing of 36 known or putative CRC susceptibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 46 publications
1
30
1
1
Order By: Relevance
“…The present analyses also identified five patients in group U (3%) with two potential pathogenic variants in different genes. This is consistent with the results of previous studies, which have reported rates of between 0.1 and 3% [7, 1618] or up to 7.5%, when potentially pathogenic missense mutations were included [19]. These cases may involve digenic inheritance, co-inheritance of genetic modifiers, or clear pathogenic mutations [20, 21].…”
Section: Discussionsupporting
confidence: 92%
“…The present analyses also identified five patients in group U (3%) with two potential pathogenic variants in different genes. This is consistent with the results of previous studies, which have reported rates of between 0.1 and 3% [7, 1618] or up to 7.5%, when potentially pathogenic missense mutations were included [19]. These cases may involve digenic inheritance, co-inheritance of genetic modifiers, or clear pathogenic mutations [20, 21].…”
Section: Discussionsupporting
confidence: 92%
“…In conclusion, MMRd rates and prevalences of LS and LLS in our study are similar to the ranges reported in 21 other studies on the incidence of these syndromes in early-onset nonpolyposis CRC (Table 4). [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] Of note, the incidence of LS was higher when the age at CRC diagnosis used as a cutoff to define "early-onset" was lower, when there was a family history of CRC, and when the molecular algorithm for MMRd: tumor MMR deficiency tested by MSI (*), IHC of MMR proteins (**), or both (***).…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, another meta-analysis suggests that pathogenic variants in BRCA1 increase CRC risk (OR = 1.56) but not in BRCA2 [ 111 ]. Another gene that deserves attention in this section is TP53 , where pathogenic variants have been recurrently found in familial/early onset and unselected CRC patients [ 3 , 4 , 5 , 6 , 28 , 32 , 102 , 112 , 113 , 114 , 115 ]. As occurs with other non-CRC genes, the debate about TP53 ’s causal role in CRC predisposition is open for discussion.…”
Section: Non-crc Hereditary Cancer Genesmentioning
confidence: 99%
“…While estimates indicate that approximately 14% of all colorectal cancer (CRC) patients have at least one first-degree relative affected with the same tumor type [ 1 , 2 ], 4–8% of all CRC patients carry germline pathogenic variants in one of the known high penetrance genes for this tumor [ 3 , 4 , 5 , 6 ], with a relevant proportion of the familial aggregation of CRC remaining unexplained. The identification of a germline pathogenic variant in a colorectal cancer-predisposing gene has important consequences for the patients and their relatives, as they can be counseled and managed based on gene-specific guidelines.…”
Section: Introductionmentioning
confidence: 99%